Osteoprotegerin is a significant prognostic factor for overall survival in patients with primary systemic amyloidosis independent of the Mayo staging - Kastritis, E.; Gavriatopoulou, M.; Dimopoulos, M.A.; Eleutherakis-Papaiakovou, E.; Kanellias, N.; Roussou, M.; Pamboucas, C.; Toumanidis, S.T.; Terpos, E. (Blood Cancer Journal, 2015)
Bone metabolism has not been systematically studied in primary (AL) amyloidosis. Thus we prospectively evaluated bone remodeling indices in 102 patients with newly diagnosed AL amyloidosis, 35 healthy controls, 35 newly diagnosed myeloma and 40 monoclonal gammopathy of undetermined significance patients. Bone resorption markers (C-telopeptide of type-1 collagen, N-telopeptide of type-1 collagen) and osteoclast regulators (soluble receptor activator of nuclear factor-κB ligand (sRANKL), osteoprotegerin (OPG)) were increased in AL patients compared with controls (P<0.01), but bone formation was unaffected. Myeloma patients had increased bone resorption and decreased bone formation compared with AL patients, while sRANKL/OPG ratio was markedly decreased in AL, due to elevated OPG in AL (P<0.001). OPG correlated with N-terminal pro-brain natriuretic peptide (P<0.001) and was higher in patients with cardiac involvement (P = 0.028) and advanced Mayo stage (P = 0.001). OPG levels above the upper value of healthy controls was associated with shorter survival (34 versus 91 months; P = 0.026), while AL patients with OPG levels in the top quartile had very short survival (12 versus 58 months; P = 0.024). In Mayo stage 1 disease, OPG identified patients with poor survival (12 versus 460 months; P = 0.012). We conclude that increased OPG in AL is not only a compensation to osteoclast activation but may also reflect early cardiac damage and may identify patients at increased risk of death within those with earlier Mayo stage.